2014
DOI: 10.1515/cclm-2013-0705
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biobanking conditions on short-term stability of biomarkers in human serum and plasma

Abstract: Based on these results, we provide recommendations for storage conditions of up to 90 days for several biomarkers. Generally, storage at ≤-80 °C for at least 90 days including occasional short-term thermal exposure is an excellent storage condition for most biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 12 publications
3
47
0
2
Order By: Relevance
“…The first studies of human complement stability were undertaken in the early part of the 20th century and these studies showed variable results for human sera stored at refrigerator and room temperatures. Recent studies have shown human complement in serum to be stable for several years at temperatures below −70 ° C, but there have been no studies on the storage loss of hemolytic activity at other temperatures since 1970 . The 1961 study of Polley and Mollison showed undiluted serum stored at −20°C for 2 months still induced classical‐pathway complement‐mediated hemolysis.…”
Section: Comparison Of Methods Between Studies Of Polley and Mollison mentioning
confidence: 99%
See 1 more Smart Citation
“…The first studies of human complement stability were undertaken in the early part of the 20th century and these studies showed variable results for human sera stored at refrigerator and room temperatures. Recent studies have shown human complement in serum to be stable for several years at temperatures below −70 ° C, but there have been no studies on the storage loss of hemolytic activity at other temperatures since 1970 . The 1961 study of Polley and Mollison showed undiluted serum stored at −20°C for 2 months still induced classical‐pathway complement‐mediated hemolysis.…”
Section: Comparison Of Methods Between Studies Of Polley and Mollison mentioning
confidence: 99%
“…In nonimmunohematology serology the stability of complement appears also to be poorly understood, with Lachmann stating that it “is, perhaps, surprising that there is relatively little literature on the topic of how serum should be prepared in order to perform functional complement assays … it is apparent that good practice in this area is not always followed, even by complementologists, let alone by companies developing diagnostic tests.” The topic of complement stability was recently partially revisited by Yang and colleagues, who found complement to be stable at very low storage temperatures (−80°C), but did not assess higher temperature ranges. Others have examined the storage of complement in serum and find evidence of complement activation (deterioration) during storage, but did not undertake any functional (lytic) assays …”
Section: Comparison Of Methods Between Studies Of Polley and Mollison mentioning
confidence: 99%
“…Finally, to promote the importance of preanalytical phase and encourage the research in that area of laboratory medicine, the WG-PRE has established the Walter Guder Preanalytical Award, which is granted to young scientists for their significant contributions to improvement of the preanalytical phase. Two awards have already been made: the first one in 2014 during the 3rd EFLM-UEMS European Joint Congress in Liverpool to Dr. Johannes Zander from Germany for a study entitled "Effect of biobanking conditions on short-term stability of biomarkers in human serum and plasma" [45] and the second one in 2016 during the 4th EFLM-UEMS European Joint Congress in Warsaw to Niamh Daly from Ireland for the study entitled "Impact of implementing preanalytical laboratory standards on the diagnosis of gestational diabetes mellitus: a prospective observational study" [46].…”
Section: Educational Meetings and Other Activitiesmentioning
confidence: 99%
“…Diferentes estudios han demostrado que el tiempo y la temperatura tienen un efecto importante sobre la estabilidad de los metabolitos [44][45][46][47] . Sin embargo, el almacenamiento a -80 ˚C o en nitrógeno líquido ha mostrado una mejor estabilidad para diferentes biomoléculas en suero y plasma 34, 48,49 .…”
Section: Almacenar a Temperatura Adecuadaunclassified